Normal mitochondrial malic enzyme levels in Friedreich's ataxia fibroblasts. Issue 11 (November 1983) - Chamberlain, S; Lewis, P D
Abstract : Normal levels of mitochondrial malic enzyme were found in fibroblasts from three patients with Friedreich's ataxia.